The Potential of Trichoderma AA1 and AA2 as Local Indonesian Cellulolytic Inoculum in the Fermentation of Gliricidia sepium Leaf Meal - A. M. W. Mulyono; M. Husein (Journal of Global Innovations in Agricultural Sciences)
The study aimed to test the cellulolytic ability of Trichoderma AA1 and AA2 inoculum as local Indonesian isolates and their application in the fermentation of Gliricidia sepium leaf meal. Measurement of cellulolytic ability includes qualitative cellulase activity (measurement of clear zone formation around fungal colonies) and quantitative cellulase activity (measurement of the amount of reducing sugar produced by broth enzymes from fungal cultures). Experiments of Gliricidia sepium fermentation using Trichoderma AA1 and AA2 were each designed using Completely Randomized Design. The treatments used consisted of fermentation duration of 0 (control), 2, 4, and 6 days—identification of Trichoderma AA1 and AA2 species using molecular identification method. The research results show that qualitative cellulase activities in Trichoderma AA2 were significantly higher compared to Trichoderma AA1. The CZD/CD ratio of Trichoderma AA1 and AA2 were 2.39±0.11 and 1.97±0.10, respectively. The CMC-ase activity of Trichoderma AA2 was 0.332±0.038 µmol/ml/min, and this was significantly higher compared to TrichodermaAA2, which was only 0.201±0.021 µmol/ml/min. Gliricidia sepium fermentation using AA1 and AA2 inoculum showed increased nutritional value, including soluble protein content, In-vitro digestibility of dry matter, and In-vitro digestibility of organic matter in 2 and 4 days of fermentation. There was a decrease in nutritional value in 6 days of fermentation. Trichoderma AA1 and AA2 were identified as Trichoderma koningiopsis and Trichoderma asperellum, respectively. The study concluded that T. Koningiopsis AA1 and T. Asperellum AA2 were proven to have cellulolytic abilities and could be used as inoculum in Gliricidia sepium fermentation to increase its nutritional value.